2008
DOI: 10.1038/sj.cgt.7701120
|View full text |Cite
|
Sign up to set email alerts
|

Cisplatin enhances the antitumor effect of tumor necrosis factor-related apoptosis-inducing ligand gene therapy via recruitment of the mitochondria-dependent death signaling pathway

Abstract: Despite adequately expressing tumor necrosis factor-related apoptosis-inducing ligand (TRAIL) receptors DR4/DR5, malignant cells are frequently refractory to the cytotoxic effect of this apoptosis-inducing ligand. The susceptibility of cancer cells to TRAIL can be potentiated by cisplatin (CDDP). This study was designed to evaluate the ability of cisplatin to enhance the cytotoxic effect of TRAIL gene therapy using the recombinant adenovirus-mediated tumor-selective expression of membrane-bound green fluoresce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
34
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 50 publications
1
34
0
Order By: Relevance
“…Thus, it is important to find therapeutic agents capable of sensitizing resistant cancer cells to TRAIL-induced apoptosis. There are many studies demonstrating that the combination of different anticancer agents with TRAIL induces additive or synergistic tumor cell death (Griffith and Kemp, 2003;Elrod and Sun, 2008;Shamimi-Noori et al, 2008;Siegelin et al, 2009). It has been demonstrated that the efficacy of histone deacetylase inhibitors in sensitizing hepatocellular carcinoma (HCC) cells to TRAIL induced apoptosis (Carlisi et al, 2009).…”
mentioning
confidence: 99%
“…Thus, it is important to find therapeutic agents capable of sensitizing resistant cancer cells to TRAIL-induced apoptosis. There are many studies demonstrating that the combination of different anticancer agents with TRAIL induces additive or synergistic tumor cell death (Griffith and Kemp, 2003;Elrod and Sun, 2008;Shamimi-Noori et al, 2008;Siegelin et al, 2009). It has been demonstrated that the efficacy of histone deacetylase inhibitors in sensitizing hepatocellular carcinoma (HCC) cells to TRAIL induced apoptosis (Carlisi et al, 2009).…”
mentioning
confidence: 99%
“…Activation of this pathway involved the cleavage of BH3 interacting death domain and mitochondrial outer membrane permeabilization, resulting in the release of cytochrome c from mitochondria, which sequentially activates caspase-9 and -3. Shamimi-Noori S et al revealed that cisplatin/TRAIL-induced cytotoxicity of thoracic cancer cells was completely abrogated either by the selective caspase-9 inhibitor or by transient knockdown of caspase-9 by siRNA, indicating that this apoptotic process was caspase-mediated and mitochondria-dependent (22). In the present study, we investigated the signaling cascades of apoptosis after the combination of TRAIL and cisplatin by Western blotting.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, the inhibitory rates of combinations of TRAIL plus chemotherapeutic drugs were higher than TRAIL alone and chemotherapeutic drug alone (P=0.000), which suggested that concomitant TRAIL and chemotherapeutic drugs could shed light on the synergy effect in inducing tumor cell apoptosis. Shamimi-Noori et al (37) demonstrated that DDP interacted with TRAIL to mediate profound activation of caspase cascade via recruitment of the mitochondriadependent death signaling pathway, whereas the increased effectiveness of caspase-8 recruitment to and activation at the death-inducing signaling complex (DISC) and the consequent shift in the ratio of caspase-8 to cellular FLICEinhibitory protein (cFLIP) at the DISC may be a potential mechanism for TRAIL sensitization by 5-FU (38). In addition, some other drugs, such as phosphatidylinositol 3-kinase inhibitor, and non-steroidal anti-inflammatory drugs also enhanced the apoptotic effect of TRAIL (39,40).…”
Section: Discussionmentioning
confidence: 99%